10-Year Retrospective Review of the Etiologies for Meningitis With Elevated Adenosine Deaminase in Cerebrospinal Fluid: Etiologies Other Than TB - Song, Joomee; Kim, Si-Ho; Jung, Yi-Rang; Choe, Junsu; Kang, Cheol-In; Min, Ju-Hong (Frontiers in Cellular and Infection Microbiology, 2022)
Purpose. An elevated adenosine deaminase (ADA) level in the cerebrospinal fluid (CSF) is considered a reliable marker of tuberculous meningitis (TBM). However, CSF-ADA levels can also be elevated in other diseases. We aimed to find the most common diagnosis of patients with elevated CSF-ADA levels. Methods. We retrospectively investigated the diagnoses of all patients with elevated CSF-ADA (ADA ≥10 IU/L) levels between 2010 and 2019 at the Samsung Medical Center. Definite TBM was defined based on microbiological evidence. Typical clinical manifestations that improved after standard TB treatment were designated as clinical TBM. We compared the laboratory characteristics of the three most common diagnoses. Results. CSF-ADA levels were elevated in 137 (5.6%) of 2600 patients. The most common diagnoses included hematologic malignancy (HM; n=36, 26.2%), TBM (n=26, 19.0%) and viral meningitis (VM; n=25, 18.2%). CSF-ADA levels did not differ significantly between TBM [median (IQR), 20.2 IU/L (13.8 – 29.3)] and HM [16.5 (12.8 – 24.0)]. However, CSF-ADA levels were lower in VM [14.0 (11.0 – 16.1)] than in TBM (p=0.027). Lymphocyte-dominant pleocytosis was more common in VM [77.0% (70.8 – 81.5)] than in TBM [16.0 (3.0 – 51.0), p=0.015] or HM [36.0 (10.0 – 72.0); p=0.032]. Interestingly, the CSF characteristics of clinical TBM were similar to those of VM, but not definite TBM. Conclusion. The most common diagnoses with elevated CSF-ADA levels were HM, followed by TBM, and VM. Clinicians should carefully consider the differential diagnoses in patients with elevated CSF-ADA levels, especially those in early stage of meningitis without microbiological evidence for TBM.